High emotional contagion and empathy are associated with enhanced detection of emotional authenticity in laughter - Neves, L. (2018)
Nonverbal vocalisations such as laughter pervade social interactions, and the ability to accurately interpret them is an important skill. Previous research has probed the general mechanisms supporting vocal emotional processing, but the factors that determine individual differences in this ability remain poorly understood. Here, we ask whether the propensity to resonate with others’ emotions—as measured by trait levels of emotional contagion and empathy—relates to the ability to perceive different types of laughter. We focus on emotional authenticity detection in spontaneous and voluntary laughs: spontaneous laughs reflect a less controlled and genuinely felt emotion, and voluntary laughs reflect a more deliberate communicative act (e.g., polite agreement). In total, 119 participants evaluated the authenticity and contagiousness of spontaneous and voluntary laughs and completed two self-report measures of resonance with others’ emotions: the Emotional Contagion Scale and the Empathic Concern scale of the Interpersonal Reactivity Index. We found that higher scores on these measures predict enhanced ability to detect laughter authenticity. We further observed that perceived contagion responses during listening to laughter significantly relate to authenticity detection. These findings suggest that resonating with others’ emotions provides a mechanism for processing complex aspects of vocal emotional information.